POPULASI BAKTERI, HISTOLOGI, KELANGSUNGAN HIDUP DAN PERTUMBUHAN BENIH IKAN GABUS (Channa striata) YANG DIPELIHARA DALAM MEDIA DENGAN PENAMBAHAN PROBIOTIK - Wirati Parameswari; Ade Dwi Sasanti; Muslim . (Jurnal Akuakultur Rawa Indonesia, 2013)
ABSTRACT The aims of this research was to determine the effect of probiotics in population bacteria intestinal, histology, survival rate and growth of snakehead. The research was carried out for 30 days of maintenance in a trap as a media container maintenance. This research used the method of completely randomized design with six treatments and repeated in three times. The treatments are W0 (control or without probiotic), W1 (2.5 µl.l-1 week-1), W2 (5 µl.l-1 week-1), W3 (7.5 µl.l-1 week-1), W4 (10 µl.l-1 week-1) dan W5 (12.5 µl.l-1 week-1). The result of the research showed that addition of probiotic in media of snakehead (C. striata) obtained the best dose is 10 μl.l-1 week-1, which can have to reduce the population of phatogenic bacteria in intestinal and had a good effect for survival rate (93.33%). As for the histopathologic known that probiotics do not give significantly different effect.   Key word:  population bacteria, histology, snakehead fry, probiotic.